A Multicenter Randomized Double-blind Study of Enoxaparin Compared with Unfractionated Heparin in the Prevention of Venous Thromboembolic Disease in Elderly In-patients Bedridden for an Acute Medical Illness - Bergmann, Jean-Fraçois; Neuhart, Eric (Thrombosis and Haemostasis, 1996)
A multicenter, randomized double-blind study compared in two parallel groups the efficacy and safety of a low molecular weight heparin (LMWH) enoxaparin 20 mg once daily, with unfractionated heparin (UFH) 5000 IU twice daily, administered subcutaneously for 10 days, in the prevention of venous thrombosis disease in 442 hospitalized elderly patients bedridden for an acute medical illness. The main efficacy endpoint was defined as the occurrence of venous thrombosis, diagnosed by a daily fibrinogen uptake test, and/or documented clinical pulmonary embolism.Intention-to-treat analysis of efficacy showed that the incidence of venous thromboembolic events was low: 4.8% (10/207) in the LMWH group (9 episodes of isotopic venous thrombosis and one of scintigraphic pulmonary embolism), and 4.6% (10/216) in the UFH group (10 episodes of isotopic venous thrombosis). The two treatments were equivalent, where equivalence was defined as a maximum difference of 7% between the two groups (p = 0.0005).There were no significant differences in terms of safety between the 216 patients in the LMWH group and the 223 patients in the UFH group who received at least one injection of the randomized treatment. During the study period, 15 patients (3.4%) died (7 in the LMWH group and 8 in the UFH group): 2 sudden deaths, one in each group, including one case in which pulmonary embolism could not be excluded since no autopsy was performed, and 13 others deaths unrelated to the study treatments. Six patients (1.4%) presented a bleeding complication: 2 (0.9%) in the enoxaparin group (one major and one minor hemorrhage), and 4 (1.8%) in the UFH group (2 major and 2 minor hemorrhages).These results indicate that subcutaneous enoxaparin 20 mg once daily for 10 days is as effective and well tolerated as subcutaneous UFH 5000 IU twice daily in the prevention of venous thromboembolic disease in bedridden elderly in-patients presenting an acute medical illness.